2017
DOI: 10.1080/21681805.2017.1362032
|View full text |Cite
|
Sign up to set email alerts
|

Associations between statin use and progression in men with prostate cancer treated with primary androgen deprivation therapy

Abstract: In the current study, statin use at time of PCa diagnosis was unrelated to time to progression in men primarily treated with ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…A total of 66 articles were excluded after the review of abstracts, and 35 studies were potentially eligible and evaluated in detail. Overall, nine studies with 101 773 patients were identified that were eligible for inclusion in the meta‐analysis . Specifically, three studies were related to abiraterone or enzalutamide, whereas the rest six articles were about ADT .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 66 articles were excluded after the review of abstracts, and 35 studies were potentially eligible and evaluated in detail. Overall, nine studies with 101 773 patients were identified that were eligible for inclusion in the meta‐analysis . Specifically, three studies were related to abiraterone or enzalutamide, whereas the rest six articles were about ADT .…”
Section: Resultsmentioning
confidence: 99%
“…However, another meta‐analysis demonstrated that such a potentially beneficial effect of statins on PCa was only found in the patients receiving radiotherapy, but not in those who accepted radical prostatectomy . Intuitively, whether the effect of statins on PCa could vary along with treatment modality arouses increasing attention in clinical practice …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain mutations in the EGFR TK domain is one of the factors lead to the resistance to certain TKIs [14]. However, on the other hand, more and more studies showed that the genetic alterations are present in only a minority of patients who partially respond to treatment and are rare in tumors other than NSCLC [15, 26, 27]. Thus, the sensitivity of only a few tumors to EGFR TKIs can be explained by the presence of EGFR TK domain mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that statins may enhance the therapeutic effect of ADT. In contrast, one recent Danish study [20] failed to find any differences in progression-free survival or risk of progression between statin users and non-users in PCa patients primarily treated with ADT. Prostate cancer is known to be dependent on androgens and ADT is commonly used to manage advanced prostate 0.00 0.50 cancer.…”
Section: Discussionmentioning
confidence: 75%